Non-participation in breast cancer screening for women with chronic diseases and multimorbidity: a population-based cohort study. Issue 1 (December 2015) - Jensen, L.; Pedersen, A.; Andersen, B.; Vestergaard, M.; Vedsted, P.
Abstract Background Chronic diseases and multimorbidity are common in western countries and associated with increased breast cancer mortality. This study aims to investigate non-participation in breast cancer screening among women with chronic diseases and multimorbidity and the role of time in this association. Method This population-based cohort study used regional and national registries. Women who were invited to the first breast cancer screening round in the Central Denmark Region in 2008–09 were included (n = 149, 234). Selected chronic diseases and multimorbidity were assessed up to 10 years before the screening date. Prevalence ratios (PR) were used as an association measure. Results The results indicated that women with at least one chronic condition were significantly more likely not to participate in breast cancer screening. In adjusted analysis, a significantly higher likelihood of non-participation was found for women with cancer (PR = 1.50, 95 % CI: 1.40–1.60), mental illness (PR = 1.51, 95 % CI: 1.42–1.60), chronic obstructive pulmonary disease (PR = 1.51, 95 % CI: 1.42–1.62), neurological disorders (PR = 1.24, 95 % CI: 1.12–1.37) and kidney disease (PR = 1.70, 95 % CI 1.49–1.94), whereas women with chronic bowel disease (PR = 0.75, 95 % CI 0.65–0.88) were more likely to participate than women without these disease. Multimorbidity was associated with increased non-participation likelihood. E.g. having 3 or more diseases was associated with 58 % increased non-participation likelihood (95 % CI: 27–96 %). Higher non-participation was also observed for women with severe multimorbidity (PR = 1.53, 95 % CI: 1.23–1.90) and mental-physical multimorbidity (PR = 1.54, 95 % CI: 1.36–1.75). Conclusion In conclusion, we found a strong association between non-participation in breast cancer screening for some chronic diseases and for multimorbidity. The highest propensity not to participate was observed for women with hospital contacts related to the chronic disease in the period closest to the screening date.